Comparitive study of predictive controllers for trajectory tracking of non-holonomic mobile robot - Kizhakke Illom, Rahul Sharma; Dušek, František; Honc, Daniel (IEEE (Institute of Electrical and Electronics Engineers), 2017)
The paper deals with predictive control of non-holonomic mobile robot. The basic nonlinear kinematic equation is linearized into two different linear time varying models based on frame of reference-world coordinates and local coordinate of mobile robot. The non-linear model predictive control is applied to the trajectory tracking problem of a non-holonomic mobile robot with these models. The control law is derived from a cost function which penalizes the state tracking error, control effort and terminal state deviation error. Various simulation experiments are conducted and a comparative analysis has been made with respect to state-of-the-art approaches.
Studie prediktivních regulátorů pro řízení dvoukolového mobilního robota
Keywords: predictive control; mobile robot; non-holonomic; trajectory tracking; prediktivní řízení; mobilní robot; dvokolový; sledování trajektorie